Effectiveness of the use of a learning model and concentrated schedule in observational learning of a new bimanual coordination pattern - Hirose, T.; Tsutsui, S.; Okuda, S.; Imanaka, K. (International Journal of Sport & Health Science, 2004)
The present research examined the interaction between the skill level of a model (an expert or learning model) and a learning schedule (alternating observation and practice; or concentrated observation and practice, respectively) on acquiring a new bimanual pattern of 90 degrees relative phase. Five groups were compared: alternating-expert, alternating-learning, concentrated-expert, concentrated-learning and physical practice only. The concentrated-learning group performed better than alternating-expert, alternating-learning, as well as physical practice only learning schedule groups in retention tests. This seemed to arise from the effectiveness of concentrated bservation throughout the improvement processes exhibited by the learning model.